Ethnocentrism in Polish Consumer Food Behaviour as a Determinant of Short Supply Chain Development - Hanus, Gabriela (European Journal of Sustainable Development, 2020)
The main purpose of this research is to investigate the phenomenon of ethnocentrism in the food behaviour of Poles as a possible determinant of the development of short supply chains. For this purpose, primary and secondary tests were carried out. The primary studies examine the level of ethnocentrism in the food behaviour of Poles, while secondary data analysis focuses on finding a relation between this phenomenon and the development of short supply chains. The primary source of the survey consists in the results of an online and distributed survey covering the whole of Poland. A total of 660 people took part in the study. The main secondary sources used in the work include the latest publications in peer-reviewed scientific journals. Across the studies covered by this paper it was found that ethnocentrism is clearly observable in the food behaviours of Poles and it might have significant influence on the development of short supply chains. Keywords: ethnocentrism; short supply chain; food behaviour